2018
DOI: 10.3126/botor.v11i0.21030
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of crude extracts of Dendrobium amoenum and detection of bioactive compounds by GC-MS

Abstract: Dendrobium amoenum is an epiphytic orchid used as tonic because it has many derivatives of phenols. The crude extract of this orchid has been shown to have antioxidant activity. The objectives of this research are to explore the cytotoxic activity of antioxidant-rich crude extract against the human cervical carcinoma and glioblastoma cell lines by MTT assay and to detect the compounds by GC-MS. Methanol (DAM) extract of D. amoenum showed high cell growth inhibition percentage against the tested cell lines. DAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
4
2
Order By: Relevance
“…The result clearly indicated that the extracts have some cytotoxic compounds, but other compounds are also present that may attribute to the cytotoxic capacity of the extracts as compared to the cisplatin. Previous reports enlightened that the methanol extract of some Dendrobium species showed cytotoxicity toward the HeLa and U251 cell lines [32,33,44]. Our results support the previous studies, which showed that polyphenol derivatives are responsible for the induction of apoptosis in cancer cells [45].…”
Section: Resultssupporting
confidence: 92%
“…The result clearly indicated that the extracts have some cytotoxic compounds, but other compounds are also present that may attribute to the cytotoxic capacity of the extracts as compared to the cisplatin. Previous reports enlightened that the methanol extract of some Dendrobium species showed cytotoxicity toward the HeLa and U251 cell lines [32,33,44]. Our results support the previous studies, which showed that polyphenol derivatives are responsible for the induction of apoptosis in cancer cells [45].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, studies have reported the presence of cholesterol 3-O[(2-acetoxy) ethyl] at a rate of 0.37% in Dendrobium amoenum. 48 However, our study shows that the presence of cholesterol at a rate of 13% in the plant is higher than that found in D. amoenum. On the other hand, literature surveys have shown that DL-glyceraldehyde is not detected in orchid plants.…”
Section: Discussioncontrasting
confidence: 73%
“…vomeracea. Previous studies have reported that Dendrobium amoenum contains 26.95% oleic acid, while Dendrobium aphyllum contains 8.6% oleic acid in its leaf methanol extract . Furthermore, Lusia tenuifolia was found to contain 1.9% oleic acid .…”
Section: Discussionmentioning
confidence: 84%
“…Their antibacterial, antifungal [ 28 ], insecticidal, antimicrobial [ 36 , 37 ], and preservative properties [ 27 ] have been reported. Six different types of fatty acid esters were identified in both methanol extracts with reported antioxidant, thyroid inhibitor [ 33 ], anticancer [ 34 ], anti-inflammatory [ 32 ], hemolytic, antiandrogenic, lubricant, pesticide, nematicide, hypocholesterolemic [ 30 ], and dienophilic [ 31 ] activities. Stigmasterol and β -sitosterol were only identified phytosterols with a wide range of pharmacological activities such as antimicrobial, anticancer, diuretic, anti-inflammatory, antioxidant, antiasthma, hepatoprotective, and anticancer activities [ 30 , 33 ].…”
Section: Resultsmentioning
confidence: 99%